Pengaruh Sustainability Reporting dan Good Corporate Governance terhadap Financial Performance - Diva Alamdqiyah; Mahroji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to explore the relationship between sustainability and good corporate governance (GCG) on the financial performance of energy and basic materials sector companies listed on the Indonesia Stock Exchange (BEI) from 2020 to 2022. In this research there are 21 companies that have been selected using purposive sampling criteria with a total of 63 data populations studied during the research period. The data used uses secondary data in the form of financial reports and sustainability reports obtained from the official websites of each company as well as on the website www.ojk.co.id. To analyze the data, use descriptive analysis, with classic assumption tests such as data normality tests, multicollinearity, autocorrelation, heteroscedasticity and hypothesis tests such as the simultaneous/f test to the partial/t test with multiple linear regression analysis methods which are used to see the influence of the independent variable sustainability and corporate governance. The research found that there is a positive and significant relationship between sustainability disclosure and company financial performance, either simultaneously or partially. Companies that are more active in disclosing sustainability-related information tend to have better financial performance, as this attracts more attention from stakeholders, including investors and customers. Using stakeholder theory and agency theory approaches, this research investigates how the implementation of sustainability and good corporate governance (GCG) affects company profitability.